2014
DOI: 10.1007/s12040-014-0427-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of tsunami deposits off southeast coast of India from the 2004 Indian Ocean tsunami: Rock magnetic and geochemical approach

Abstract: Indian Ocean Tsunami (IOT) had a major impact on the geomorphology and sedimentology of the east coast of India. Estimation of the magnitude of the tsunami from its deposits is a challenging topic to be developed in studies on tsunami hazard assessment. Two core sediments (C1 and C2) from Nagapattinam, southeast coast of India were subjected to textural, mineral, geochemical and rock-magnetic measurements. In both cores, three zones (zone I, II and III) have been distinguished based on mineralogical, geochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 74 publications
1
6
0
1
Order By: Relevance
“…In natural geologic materials, magnetic susceptibility is dependent on the concentration, mineralogy, and grain size of the magnetomineralogical assemblage [Evans and Heller, 2003;Liu et al, 2012]. These factors are usually modulated by nonmagnetic characteristics of sediments, such as dilution by a paramagnetic or diamagnetic matrix [Rey et al, 2000;Font et al, 2010;Maher, 2011;Veerasingam et al, 2014] and mineralogical changes [e.g., Watkins and Maher, 2003;Larrasoaña et al, 2008;Kissel et al, 2016]. Magnetic minerals and trace metals also show some dependence, although unclear relationships exist in marine sediments [e.g., Chan et al, 2001;Rubio et al, 2001;Wehland et al, 2002;Hu et al, 2003;Davila et al, 2006;Prajith et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…In natural geologic materials, magnetic susceptibility is dependent on the concentration, mineralogy, and grain size of the magnetomineralogical assemblage [Evans and Heller, 2003;Liu et al, 2012]. These factors are usually modulated by nonmagnetic characteristics of sediments, such as dilution by a paramagnetic or diamagnetic matrix [Rey et al, 2000;Font et al, 2010;Maher, 2011;Veerasingam et al, 2014] and mineralogical changes [e.g., Watkins and Maher, 2003;Larrasoaña et al, 2008;Kissel et al, 2016]. Magnetic minerals and trace metals also show some dependence, although unclear relationships exist in marine sediments [e.g., Chan et al, 2001;Rubio et al, 2001;Wehland et al, 2002;Hu et al, 2003;Davila et al, 2006;Prajith et al, 2015].…”
Section: Introductionmentioning
confidence: 99%
“…Grain‐size analyses revealed high amounts of medium to coarse sand and gravel indicating high‐energy conditions (e.g., Goff & Chagué‐Goff, ; Veerasingam et al., , Vött et al., ; Yu, Zhao, Shi, & Meng, ), especially when compared to silt‐dominated deposits of the quiescent and sheltered Roman harbor. Modern tsunami research has shown, for example, that onshore sand sheets are typical deposits associated with tsunami landfall (e.g., Shi, Dawson, & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Modern tsunami research has shown, for example, that onshore sand sheets are typical deposits associated with tsunami landfall (e.g., Shi, Dawson, & Smith, ). Moreover, the sand layers encountered in the Alkinoos Harbor basin show distinct peaks of the Ca/Fe ratio due to increasing input of calcium carbonate from the marine side in the form of shell debris and (micro)faunal tests (e.g., Goff & Chagué‐Goff, ; Mathes‐Schmidt et al., ; Sakuna, Szczuciński, Feldens, Schwarzer, & Khokiattiwong, ; Veerasingam et al., , Vött et al., 2011b, ). The Alkinoos record also shows sedimentary features typical of high‐energy impact such as erosional unconformities (KOR 1A, KOR 25, KOR 24A) or fining upward sequences (KOR 24A; e.g., Bahlburg & Weiss, ; Gelfenbaum & Jaffe, ; Goff & Chagué‐Goff, ; Morton, Gelfenbaum, & Jaffe, ; Shi et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, trace metals are one of the most promising sentinels of tsunamigenic deposits both during the Holocene and nowadays (Veerasingam et al, 2014;Bianchette et al, 2016). Chemical signatures of (palaeo-)tsunamis have been reviewed in the last years, with exciting perspectives for the future development of this field (Chagué-Goff, 2010;Nelson et al, 2015).…”
Section: Introductionmentioning
confidence: 99%